John Whitten papers - Whitten, John, 1842-1902.
Diary (110 pages; 1863 August 4-1865 May 17) kept by Whitten during his Civil War service with the 5th Iowa Infantry Regiment, U.S. Army. Subjects include the battles of Corinth and Jackson, Miss., the siege of Vicksburg, Miss., and Whitten's experience as prisoner of war in Belle Isle prison, Richmond, Va., in Columbia, S.C., and in Andersonville Prison, Andersonville, Ga. Also includes genealogical material and photographs, 1857-2010, of the Whitten and allied Sperry families as well as an obituary of John Whitten.
Electronic files of the Whitten and allied Sperry families genealogical material and photographs and John Whitten obituary also available through Library of Congress Manuscript Division.
Electronic files of originals in private hands.
Union soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sperry family; Sperry family -- Genealogy; Whitten family; Whitten family -- Genealogy; United States. -- Army. -- Iowa Infantry Regiment, 5th (1861-1864); Andersonville Prison; Belle Isle (Prison); Corinth, Battle of, Corinth, Miss., 1862.; Jackson, Battle of, Jackson, Miss., 1863 (May 13); Prisoners of war -- Georgia -- Andersonville; Prisoners of war -- South Carolina -- Columbia; Prisoners of war -- Virginia -- Richmond; Mississippi -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Vicksburg (Miss.) -- History -- Siege, 1863.; Soldiers